2012
DOI: 10.1177/0011128712466889
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgment, Crime Seriousness, and the Relations Between Them

Abstract: The present study analyzes the relationship between moral judgment and perceptions of crime seriousness. This analysis is done with special attention to Kohlberg's theory of moral development. Main research findings: Significant correlations exist between perceived seriousness of offenses and consideration of such conducts as immoral, and between the levels of the perceived seriousness of offenses and the levels of the moral judgment of their moral dilemmas. In addition, attitudes toward various moral dilemmas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 78 publications
1
13
0
2
Order By: Relevance
“…Roberts et al (1996) found that adults often knew about the core parts of the Canadian rape law reform even if their knowledge of sexual crime in general was low. The perceived seriousness of a behaviour affects whether it is regarded as a crime or not (Herzog & Einat, 2012;Houston & Hwang, 1996), and rape is most likely perceived as being more serious than other sexual criminal behaviours. This might also explain why, in our study, rape in a relationship context was more easily identified as a sexual crime than receiving a picture of a penis.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts et al (1996) found that adults often knew about the core parts of the Canadian rape law reform even if their knowledge of sexual crime in general was low. The perceived seriousness of a behaviour affects whether it is regarded as a crime or not (Herzog & Einat, 2012;Houston & Hwang, 1996), and rape is most likely perceived as being more serious than other sexual criminal behaviours. This might also explain why, in our study, rape in a relationship context was more easily identified as a sexual crime than receiving a picture of a penis.…”
Section: Discussionmentioning
confidence: 99%
“…Path4-1jmoral judgmentseriousness of issue Herzog and Einat (2016) The relationship between moral judgment and perception of seriousness of issue has been found positive 7…”
Section: Sno Path Author Interpretationmentioning
confidence: 97%
“…Two main issues that research had focused on are, on one hand, the degree of consensus regarding crime seriousness judgments both within societies, as well as cross-culturally (Lesieur & Lehman, 1975;Cullen, Link, & Polanzi, 1982;Parton, Hansel, & Stratton, 1991;Levi & Jones, 1985;Fishman, Kraus, & Cohen, 1986;Kwan & Kwan, 2000;Herzog & Einat, 2016). While research shows that there is a substantive degree of consensus regarding the seriousness of the most and the least serious crimes, there is somewhat less agreement when it comes to crimes which fall in the midrange (Cullen, Link, Travis, & Wozniak, 1985).…”
Section: Introductionmentioning
confidence: 99%